2014
DOI: 10.1097/qai.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

HIV Self-Testing Among Online MSM in China

Abstract: HIV self-testing offers an alternative to facility-based testing that could expand HIV testing among MSM. We organized an online survey of MSM in China to better understand the frequency and correlates of HIV self-testing. A total of 1342 individuals completed the survey. 20.3% of MSM reported prior HIV self-testing. Self-testing was correlated with being married, having six or greater male anal sex partners in the past three months, and having HIV tested within 12 months in the multivariable analysis. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 24 publications
5
53
1
Order By: Relevance
“…In this study, we found that a majority of MSM participants in Jiangsu Province, China, where there is a relatively high burden of HIV infections among this population [14], had heard of HIV self-testing and 26.2% had ever self-tested for HIV, a figure similar to a previous study [11]. A majority of participants reported that performing self-testing was “somewhat easy” or “very easy.” However, participants’ confidence in the accuracy of their self-testing results was much lower where only 24.1% said they were “very confident.” In addition, a majority of participants perceived that HIV self-testing was less accurate compared to CDC or hospital provided testing.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, we found that a majority of MSM participants in Jiangsu Province, China, where there is a relatively high burden of HIV infections among this population [14], had heard of HIV self-testing and 26.2% had ever self-tested for HIV, a figure similar to a previous study [11]. A majority of participants reported that performing self-testing was “somewhat easy” or “very easy.” However, participants’ confidence in the accuracy of their self-testing results was much lower where only 24.1% said they were “very confident.” In addition, a majority of participants perceived that HIV self-testing was less accurate compared to CDC or hospital provided testing.…”
Section: Discussionsupporting
confidence: 81%
“…A systematic review of HIV self-testing among key populations in other countries found that acceptability of and preference for self-testing was very high and confidentiality and privacy were among the key facilitators of self-testing [10]. A recent study conducted among an online sample of Chinese MSM found that 20.3% of participants have ever self-tested for HIV [11]. One of the concerns of HIV self-testing is that individuals without training or supervision may incorrectly understand test instructions, incorrectly collect the specimens and incorrectly interpret the test results [10].…”
Section: Introductionmentioning
confidence: 99%
“…We found MSM who were married were more likely to test for HIV, also noted by Han et al 55 It is possible that the responsibility for their wives or family members motivates men to take HIV tests and to take precautions if they are infected. Some studies have found that younger age was associated with higher HIV testing rates.…”
Section: Discussionsupporting
confidence: 77%
“…However, many MSM do not use this service or fail to return for periodic testing due to a perceived lack of confidentiality in identity and results, long wait-times, and stigma associated with HIV testing. 28,55 Most of our participants thought “anonymity”, “confidentiality of the test results” or “rapid HIV testing” would facilitate their testing activities, while “not knowing where to test” and “perceived low risk of HIV infection” were two of the top three barriers to testing. Successful experiences have demonstrated the benefits of self-testing, such as time/location convenience, protection against privacy disclosure, and increased HIV testing frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation